THE GROWTH OF ENGLISH EDUCATION 1348-1648: A SOCIAL AND CULTURAL HISTORY (Author: Michael Van Cleave Alexander) - Perceval-Maxwell, M. (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1991)
Michael Van Cleave Alexander. THE GROWTH OF ENGLISH EDUCATION 1348-1648: A SOCIAL AND CULTURAL HISTORY. University Park: The Pennsylvania State University Press, 1990. xiii & 286 pp.